Association Between Serum High‐Density Lipoprotein Cholesterol Levels and Progression of Chronic Kidney Disease: Results From the KNOW‐CKD. Issue 6 (19th March 2019) - Nam, Ki Heon; Chang, Tae Ik; Joo, Young Su; Kim, Joohwan; Lee, Sangmi; Lee, Changhyun; Yun, Hae‐Ryong; Park, Jung Tak; Yoo, Tae‐Hyun; Sung, Su Ah; Lee, Kyu‐Beck; Oh, Kook‐Hwan; et al.
Abstract : Background: High‐density lipoprotein cholesterol (HDL‐C) levels are generally decreased in patients with chronic kidney disease (CKD). However, studies on the relationship between HDL‐C and CKD progression are scarce. Methods and Results: We studied the association between serum HDL‐C levels and the risk of CKD progression in 2168 participants of the KNOW‐CKD (Korean Cohort Study for Outcome in Patients With Chronic Kidney Disease). The primary outcome was the composite of a 50% decline in estimated glomerular filtration rate from baseline or end‐stage renal disease. The secondary outcome was the onset of end‐stage renal disease. During a median follow‐up of 3.1 (interquartile range, 1.6–4.5) years, the primary outcome occurred in 335 patients (15.5%). In a fully adjusted Cox model, the lowest category with HDL‐C of <30 mg/dL (hazard ratio, 2.21; 95% CI, 1.30–3.77) and the highest category with HDL‐C of ≥60 mg/dL (hazard ratio, 2.05; 95% CI, 1.35–3.10) were associated with a significantly higher risk of the composite renal outcome, compared with the reference category with HDL‐C of 50 to 59 mg/dL. This association remained unaltered in a time‐varying Cox analysis. In addition, a fully adjusted cubic spline model with HDL‐C being treated as a continuous variable yielded similar results. Furthermore, consistent findings were obtained in a secondary outcome analysis for the development of end‐stage renal disease. Conclusions: A U‐shaped association was observed between serum HDL‐C levels and adverse renal outcomes in this large cohort of patients with CKD. Our findings suggest that both low and high serum HDL‐C levels may be detrimental to patients with nondialysis CKD.